Controller Synthesis for Safety Critical Planning - Orlandini, Andrea; Suriano, Marco; Cesta, Amedeo; Finzi, Alberto (2013 IEEE 25th International Conference on Tools with Artificial Intelligence, 2013)
Safety critical planning and execution is a crucial issue in autonomous systems. This paper proposes a methodology for controller synthesis suitable for timeline-based planning and demonstrates its effectiveness in a space domain where robustness of execution is a crucial property. The proposed approach uses Timed Game Automata (TGA) for formal modeling and the UPPAAL-TIGA model checker for controllers synthesis. An experimental evaluation is performed using a real-world control system.